Performance Analysis of DTN Using Level Signal Priority Epidemic Routing Protocol - Zainudin, Ahmad; Sudarsono, Amang; Pambudi, Kevin Prima (EMITTER International Journal of Engineering Technology, 2015)
A DTN architecture consists of several nodes that are connected with high dynamic topology. The routing protocol is an important part which determine the DTN performance system. Although DTN is addressed to be tolerant of delay, a routing protocol with better performance will maximizing packet delivery rate and minimizing the delivery latency. This paper evaluate a level signal priority epidemic routing protocol for delay tolerant network architecture. Our system adopts DTN2 framework using classic epidemic and priority epidemic dynamic routing protocols. The performance of both dynamic routing is observed and compared based on throughput and delay of transmitted data. The measurement results show that the classic epidemic use more bandwith due to sending the same messages many times. The delay transmission using a level signal priority epidemic routing is smaller than classic epidemic routing protocol in all hops of the test-bed. Epidemic based on signal level routing could make traffic of network more efficient than classic Epidemic routing because of filtering system in node before sending bundle to neighbor node.Keywords: DTN, dynamic routing, level signal priority